2011
DOI: 10.1007/s11250-011-9946-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestibility and ruminal fermentation characteristic in swamp buffaloes fed on chemically treated rice straw and urea

Abstract: The experiment was conducted to determine effects of urea-lime-treated rice straw and urea levels in concentrate on rumen fermentation, apparent nutrient digestibility, and cellulolytic bacteria population of 4-year-old, rumen-fistulated swamp buffaloes. All animals were randomly assigned according to a 2 × 2 factorial arrangement in a 4 × 4 Latin square design to receive four dietary treatments: factor A, two sources of roughage (rice straw and 2%urea + 2%lime-treated rice straw); factor B, two levels of urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…However, it is characterized by low levels of CP and high level of structural polysaccharides, which drastically affected the DM intake, digestion and ultimate performance (Wanapat et al, 1985; Chemjon, 1991; Safari et al, 2011). Improving the utilization of low quality roughages could be by treatment with nitrogen sources, chemical and physical treatment (McDonald et al, 2002; Nguyen et al, 2012). Urea treatment of rice straw could increase its nutritive value (Sundstøl et al, 1978; Abate and Melaku, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is characterized by low levels of CP and high level of structural polysaccharides, which drastically affected the DM intake, digestion and ultimate performance (Wanapat et al, 1985; Chemjon, 1991; Safari et al, 2011). Improving the utilization of low quality roughages could be by treatment with nitrogen sources, chemical and physical treatment (McDonald et al, 2002; Nguyen et al, 2012). Urea treatment of rice straw could increase its nutritive value (Sundstøl et al, 1978; Abate and Melaku, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of dietary concentrate decreased relative abundance of Fibrobacteraceae in the solid (de Menezes et al, 2011) and liquid fraction (Thoetkiattikul et al, 2013). Greater urea content in iso-nitrogenous protein supplements (65 mg N/kg BW) fed to swamp buffalo consuming rice straw (2% CP) increased cellulolytic species determined by roll-tube technique (Nguyen et al, 2012). However, no change in absolute abundance of F. succinogenes was detected by real-time PCR with the increase in urea.…”
Section: Discussionmentioning
confidence: 93%
“…The combination of using urea-lime-treated rice straw and fed with concentrate feed (4% urea) has ability to improve rumen ecology, rumen fermentation efficiency, and nutrient digestibility in swamp buffaloes as reported by Nguyen et al (2012). Hue et al (2008) reported that on feeding sheep with urea treated rice straw as a based diet, the commercial concentrate could be replaced by protein source feed, such as cassava and jackfruit foliage.…”
Section: Physical/mechanical Treatmentmentioning
confidence: 99%